Developing the Potential of Young Entrepreneurial Interest by Utilizing Social commerce at PB Soedirman 2 Islamic Vocational School - Aghnia Wulandari; Aries Setyawan; Azzahra Dian Kinanti; Ahmad Zaky Afansah; Irin Purwanti; Satria Firman Nafis; Bayu Rizaldy; Hartati Lumban Gaol (STIE MBI, 2024)
Developing the potential interest of young entrepreneurs by utilizing Social commerce is an innovative and effective strategy in facilitating the younger generation to become successful entrepreneurs in the ever-evolving digital era. With the advancement of information technology and the wider penetration of the internet, Social commerce has become the main cornerstone in building businesses and expanding market reach. Through the use of Social commerce, young entrepreneurs have the opportunity to sell their products or services through social media platforms such as Instagram, Facebook, TikTok, and other online platforms. The use of Social commerce provides various significant benefits for young entrepreneurs. Social commerce allows them to start a business with relatively low capital. By utilizing free platforms, young entrepreneurs can market their products without having to make a large investment in physical infrastructure. Social commerce also allows young entrepreneurs to access the global market more easily, by using the right digital marketing techniques, they can reach consumers in different parts of the world without having to have a physical store in each location. In addition, the use of social commerce also provides opportunities for young entrepreneurs to continue to learn independently and develop their digital skills. With the existence of Community Service activities with the theme of Developing the Potential Interest of Young Entrepreneurs with the Utilization of Social commerce, it can encourage the spirit of young entrepreneurs, interest and creativity of students to be entrepreneurial from an early age by using Social commerce as the media used, by utilizing Social commerce students can learn how to utilize technology to develop businesses that will later be undertaken.